Jurisprudential- Legal Analysis of the Effects of Wife's Disobiedence in Temporary Marriage - reza dehghannezhad; farajollah hedayatniya (فقه و حقوق خانواده)
There is no doubt about the legitimacy of temporary marriage in Shiite jurisprudence. This kind of marriage is recognized in Iran’s civil law and family support law, and some of its ruls is indicated. But there are some ambiguities about some of the issues such as the juridical effects of the wife's disobedience. Disobedience of wife in permanent marriage could lead to loss of alimony right entitled to her but in temporary marriage wife not entitled to alimony right. So, the important question is proposed here: what is the effect of a wife’s disobedience on her rights, and in other words, what is the executive guarantee of the husband’s right to submission in temporary marriage? There is no commentary about this issue in Civil Law, while this issue is important and should be investigated. In this paper, this issue is studied through descriptive and analytical methods from a jurisprudential perspective. The findings of the study are shown that if the divorced wife refuses to obey without a valid excuse, her disobedience would be fulfilled. On other hand, disobedience of the wife in temporary marriage leads to nulling her right of marriage portion or dowry, and the husband could deduct from the dowry considering proportion to the period of disobedience, and if the husband had paid the full dowry, he should demand its return in the same proportion through the court.